2019
DOI: 10.1159/000504297
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis to Weed Pollen in Germany: Dominance by Plantain, Rising Prevalence, and Polysensitization Rates over 20 Years

Abstract: <b><i>Background:</i></b> In contrast to the 3 major aeroallergens tree pollen, grass pollen, and house dust mites, allergic rhinitis caused by herbal pollen has received comparatively little attention in recent clinical studies. Since various weeds flower during summer until fall, allergic rhinitis to weeds may be underdiagnosed and/or mistakenly diagnosed as grass pollen allergy. <b><i>Objective:</i></b> To investigate (i) the currently most frequent weed aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
4
20
0
3
Order By: Relevance
“…8 In addition, we recently published results on increasing positive SPTs in weed allergic patients from our region during the last 20 years. 9 Of note, we expected higher total sensitization rates in our current study than in populationbased studies because our study population consisted of referred patients with suspected airway allergies and our cut-off ≥2 mm for positive SPTs was lower than in most current studies. Because sensitization to aeroallergens during childhood is largely persistent and associated with polysensitization, early sensitization patterns are also strongly associated with manifestation of the asthma-rhinitis multimorbid phenotype.…”
Section: Discussionmentioning
confidence: 55%
“…8 In addition, we recently published results on increasing positive SPTs in weed allergic patients from our region during the last 20 years. 9 Of note, we expected higher total sensitization rates in our current study than in populationbased studies because our study population consisted of referred patients with suspected airway allergies and our cut-off ≥2 mm for positive SPTs was lower than in most current studies. Because sensitization to aeroallergens during childhood is largely persistent and associated with polysensitization, early sensitization patterns are also strongly associated with manifestation of the asthma-rhinitis multimorbid phenotype.…”
Section: Discussionmentioning
confidence: 55%
“…Limited data based on SPT results are available in Germany for rates of sensitization to aeroallergens. We recently published results on increasing numbers of patients with SPTs positive for weeds in our region during the last 20 years [31]. In the population-based European skin prick test study I from the GA 2 LEN community (14 countries, 2000-2001), sensitization rates for Germany were 37.9 % for grass, 37.6 % for birch, 35.9 % for hazel, and 34.8 % for alder pollen [10].…”
Section: Discussionmentioning
confidence: 99%
“…12 In agreement with the results of the present study, several investigations found an increasing trend of multisensitization to aeroallergens. 17,18 Monosensitization and multisensitization can be immunologically different. Multisensitized patients may have more severe symptoms, and are less responsive to immunotherapies.…”
Section: Discussionmentioning
confidence: 99%